Search Intensity, Cost of Living and Local Labor Markets in Britain - Eleonora Patacchini; Yves Zenou (Institute for the Study of Labor (IZA), 2003)
A model is considered in which optimal search intensity is a result of a tradeoff between short-run losses due to higher search costs (more interviews, commuting?) and long-run gains due to a higher chance of finding a job. We show that this optimal search intensity is higher in areas characterized by larger cost of living and/or higher labor market tightness. We then test this model using county-level data in England for the period 1991-2000. As predicted by the theoretical model, both the (county) cost of living and the (county) labor market tightness are found to have a positive and significant effect on the (county) search intensity. We also find positive spatial correlation between counties (i.e. clustering of counties with similar level of search intensity) and strong spatial spillover effects.
Keywords: R1; J64; C23; D83; 330; job matching; search intensities; dynamic panel data; GMM estimation; measurement errors; spatial correlation; Suchtheorie; Arbeitsuche; Schätzung; Lebenshaltungskosten; Großbritannien